2009
DOI: 10.1590/s0080-62342009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco associados ao excesso de peso entre adolescentes da Região Oeste Paulista

Abstract: The objective of this study was to analyze the association between being overweight and family risk factors in adolescents from Western Sao Paulo state. This cross-sectional study involved 1779 adolescents of both genders and with ages ranging between 11 and 17 years. The participants' body mass index was calculated, and the family risk factors were analyzed through a questionnaire. Excessive weight was associated with the male gender (CR=1.55 [1.22-1.97]), studying in a private school (CR=2.14 [1.56-2.94]) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
2
6
0
2
Order By: Relevance
“…In the first study, we found that 28.6% of 1,215 youth aged 10-17 years were classified as overweight/obese [11]. In the second study, only 22.9% of adolescents aged 11-18 years were overweight/obese [12]. Given the present transition from under-nutrition to over-nutrition, it is vital that we continue to monitor trends in child obesity within Brazil's most populace regions using internationally applicable classification systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study, we found that 28.6% of 1,215 youth aged 10-17 years were classified as overweight/obese [11]. In the second study, only 22.9% of adolescents aged 11-18 years were overweight/obese [12]. Given the present transition from under-nutrition to over-nutrition, it is vital that we continue to monitor trends in child obesity within Brazil's most populace regions using internationally applicable classification systems.…”
Section: Introductionmentioning
confidence: 99%
“…In order to design effective interventions we need an understanding of the modifiable risk factors associated with fat accretion in children. Several studies have identified key sociodemographic correlates of obesity in Brazilian children, such as sex [5,8,11,12], age [2,5,13], socioeconomic status [4,14], ethnic group [3,14], familial characteristics [14], parental education [12], and school type [3,4,8,12]. While it is important to determine which groups to target, none of the identified factors are modifiable through lifestyle intervention.…”
Section: Introductionmentioning
confidence: 99%
“…34 It is highlighted that, in this study, the participants whose mothers had a higher education level had a greater chance of gaining excess weight. Although some studies identify higher maternal education level as a protection factor against overweight in children and adolescents, [35][36] it is interesting that higher maternal education level has also been significantly associated with the habit of TV watching among adolescents, even if that variable was not assessed in this study. 37 Children and adolescent who watch TV more frequently and longer possibly have a more sedentary behavior and, therefore, are more subject to excess weight.…”
Section: Discussionmentioning
confidence: 71%
“…However, despite the frequent characterization of higher maternal level of education as a protective factor against poor quality of diet among adolescents, it is important to observe that factors associated with cardiovascular diseases (CVD) have also been connected to higher maternal levels of education [28].…”
Section: Discussionmentioning
confidence: 99%